Website-Based Design of Scholarship Information Distribution System for UNWAHA Students - Ayik Komsari; Primaadi Airlangga (NEWTON: Networking and Information Technology, 2021)
Scholarship is the provision of financial assistance needed by students who have qualified for a scholarship. Many scholarships are available both from UNWAHA and outside of UNWAHA but many do not know this scholarship information. The current system of disseminating scholarship information is still through social media while scholarship seekers have not or do not have friendships on social media. The design if the spread of this scholarship is using the waterfall method which is a method of systematic system development. The design of this scholarship information distribution system was created to accommodate scholarship information so that it can help students to directly get information easier. This scholarship information distribution system can be an alternative that makes it easier for students to get scholarships and share scholarship information. Scholarship information distribution system is incorporated in this pusatkarir.informatiUNWAHA.com site.